Case study of language development of selected kindergarteners read aloud sessions - Ting, Ying Ying (Universiti Malaysia Sarawak, UNIMAS, 2009)
The main purpose of this study was to investigate the language development of the four selected kindergarteners. The study was conducted in a private kindergarten which was under an institution of higher learning. The four kindergarteners were selected through a video recording during the second visit to the kindergarten. Selection of the children was made in consultation with and at the recommendation of the teacher. The teacher was the best person to make recommendation as the children were under her charge. Data for this study were video recordings of reading aloud sessions which were then transcribed for analysis. The video recordings were conducted from the end of July to the middle of November. A total of eighteen reading aloud sessions were recorded. Seven picture storybooks were repetitively used to read a loud to the kindergarteners. Results of the study showed that the four selected kindergarteners showed some language development through the interactive story discussion with reader during read aloud sessions. They demonstrated their understanding and knowledge based on their personal experience, background knowledge and imitation from peers and reader. Open-ended question technique and picture discussion were used on the reading aloud sessions to stimulate kindergarteners to think critically and creatively to the story. However, there was only minor language development achieved by the four kindergarteners probably because of the short period of reading sessions. The findings of this study highlighted the importance of reading aloud to children which contributed to their language development.